Monitoring air pollution effects on children (MAPEC) living near cement factories: The MAPEC_Gubbio Study - Edoardo Franceschini; Tommaso Rondini; Mattia Acito; Cristina Fatigoni; Milena Villarini; Massimo Moretti (Toxicology Letters, 2026)

Cryopreservation of fermented table olives microbiomes: an integrative case study on viability, functional stability, and biobanking applications - Katia Gialluisi; Luciana De Vero; Giuseppe Petruzzino; Laura Verrone; Giancarlo Perrone; Antonio Moretti; Vittorio Capozzi; Massimo Ferrara (Food Research International, 2026)

Six centuries (15th–21st) of environmental change and land-use in Mar Piccolo, Southern Italy: palynological and historical evidence - Gabriele Niccolini; Adele Bertini; Niccolò Degl’Innocenti; Massimo Moretti; Giuseppe Mastronuzzi (Regional Environmental Change, 2026)

Microplastic pollution in the littoral environment: insights from the largest Mediterranean Sabellaria spinulosa (Annelida) reef and shoreface sediments - Giusto Lo Bue; Maya Musa; Agnese Marchini; Maria Pia Riccardi; Stanislas F. Dubois; Stefania Lisco; Massimo Moretti; Alessia de Luca; Nicoletta Mancin (Marine Pollution Bulletin, 2025)

Holocene landscape changes and human impact in Southern Italy: A case-study from the Mar Piccolo semi-enclosed marine basin (Taranto) - Gabriele Niccolini; Adele Bertini; Niccolò Degl’Innocenti; Stefania Lisco; Massimo Moretti; Giovanni Scardino; Giuseppe Mastronuzzi (CATENA, 2025)

Early prediction of ochratoxigenic Aspergillus westerdijkiae on traditional Italian caciocavallo during ripening process by MS-based electronic nose - Salvatore Cervellieri; Francesco Longobardi; Antonia Susca; Pamela Anelli; Massimo Ferrara; Thomas Netti; Miriam Haidukowski; Antonio Moretti; Vincenzo Lippolis (Food Chemistry, 2025)

Monitoring fungi and mycotoxin potential in pistachio nuts of Turkish origin: A snap-shot for climate change scenario - Pamela Anelli; Miriam Haidukowski; Massimo Ferrara; Asli Kisikkaya; Ceyda Pembeci; Hayrettin Ozer; Giuseppina Mulè; Martina Loi; Antonio Moretti; Antonia Susca (Fungal Biology, 2024)

Genotoxicity assessment of 1,4-anhydro-4-seleno-D-talitol (SeTal) in human liver HepG2 and HepaRG cells - Raffaella di Vito; Mattia Acito; Cristina Fatigoni; Carl H. Schiesser; Michael J. Davies; Francesca Mangiavacchi; Milena Villarini; Claudio Santi; Massimo Moretti (Toxicology, 2023)

Analysis of the Sabellaria spinulosa Bioconstruction Growth in a Laboratory - Stefania Lisco; Tamara Lazic; Cataldo Pierri; Daniela Mele; Alessia de Luca; Massimo Moretti (Journal of Marine Science and Engineering, 2023)
Sabellaria spinulosa (Leukhart, 1849) is a suspension feeding polychaeta that lives in tubes consisting of terrigenous particles captured by the worm itself. They form impressive reefs containing millions of worm tubes. In temperate marine areas, under optimal environmental conditions, these structures can become natural breakwaters and can play an active role in sandy beaches’ defense. In this work, we report procedures aimed to analyze the growth of S. spinulosa bioconstructions in laboratory. By collecting biological replicas from a wild reef, this study aimed to identify sedimentological characteristics of sands that induce faster tube growth. During the tank experiments, the grain size and mineralogy of the sand were modified. By employing thin sections and X-ray microtomography analyses, the structures observed and measured during and after the tests were analogous to those naturally formed. The fastest growth was recorded in the presence of bioclastic sands with a grain size between 125 and 350 μm. Defining the physical conditions that induce faster growth is fundamental for the defense of these vulnerable habitats but also the surrounding marine environment. This study also lays the foundations for coastal protection interventions in which bioconstructions grown in the tank could be directly implanted on submerged natural and artificial substrates that are already present in situ.

In vitro toxicological assessment of PhSeZnCl in human liver cells - Raffaella di Vito; Sara Levorato; Cristina Fatigoni; Mattia Acito; Luca Sancineto; Giovanna Traina; Milena Villarini; Claudio Santi; Massimo Moretti (Toxicological Research, 2023)
Phenylselenenylzinc chloride (PhSeZnCl) is an air-stable selenolate, easily synthesizable through oxidative insertion of elemental zinc into the Se-halogen bond of the commercially available phenylselenyl chloride. PhSeZnCl was shown to possess a marked GPx-like activity both in NMR and in vitro tests, and to effectively react with cellular thiols, and was supposed for a potential use in the chemotherapy of drug-resistant cancers. However, activity of PhSeZnCl in hepatic cells has never been tested before now. In this in vitro approach, we evaluated the cytotoxic, genotoxic, and apoptotic activities, as well as the effects on cell cycle of PhSeZnCl in two preclinical hepatic models, namely HepG2 and HepaRG cells. Results showed that cell viability of HepG2 and HepaRG cells decreased in a dose-dependent manner, with a more marked effect in HepG2 tumour cells. Moreover, treatment with 50 µg/mL PhSeZnCl caused an increase of primary DNA damage (4 h) and a statistically significant increase of HepG2 cells arrested in G 2 /M phase. In addition, it altered mitochondrial membrane potential and induced chromosomal DNA fragmentation (24 h). In HepaRG cells, PhSeZnCl was able to determine a cell cycle-independent induction of apoptosis. Particularly, 50 µg/mL induced mitochondrial membrane depolarization after 24 h and apoptosis after 4 h treatment. Futhermore, all PhSeZnCl concentrations tested determined a significant increase of apoptotic cells after 24 h. Apoptosis was also highlighted by the detection of active Caspase-3 by Western Blot analysis after 24 h exposure. In conclusion, this first toxicological assessment provides new insights into the biological activity of PhSeZnCl in preclinical hepatic models that will be useful in future safety assessment investigation of this compound as a potential pharmaceutical.

A Potential Beach Monitoring Based on Integrated Methods - Isabella Lapietra; Stefania Lisco; Luigi Capozzoli; Francesco De Giosa; Giuseppe Mastronuzzi; Daniela Mele; Salvatore Milli; Gerardo Romano; François Sabatier; Giovanni Scardino; Massimo Moretti (Journal of Marine Science and Engineering, 2022)
This study focuses on the analysis of sandy beaches by integrating sedimentological, geomorphological, and geophysical investigations. The beach represents an extremely variable environment where different natural processes act simultaneously with human activities, leading to the gathering of different methodologies of the Earth Sciences to study its evolution in space and time. The aim of this research is to propose a potential procedure for monitoring the morpho-sedimentary processes of sandy beaches by analyzing the textural and compositional characteristics of the sands and quantifying the volumes involved in the coastal dynamics. The study area includes two Apulian sandy beaches (Torre Guaceto and Le Dune beach) that are representative of the coastal dynamics of a large sector of the central/northern Mediterranean Sea involving the southern Adriatic Sea and the northern Ionian Sea. Sedimentological and ecological investigations allowed to describe the textural and compositional characteristics of the beach sands by interpreting their sand provenance and the physical/biological interactions within the beach. The topographic surveys carried out with a Terrestrial Laser Scanner and an Optical Total Station, aimed to quantify the variations of sediment volume over time, whereas the Delft3d software was applied to analyze the effects of the dominant wave motion on the sedimentary dynamics. Lastly, the geophysical techniques which included Sub Bottom Profiler procedures, Ground Penetrating Radar investigation, and resistivity models enabled us to calculate the sand sediment thickness above the bedrock.

A system of marine animal bioconstructions in the mesophotic zone along the Southeastern Italian coast - Frine Cardone; Giuseppe Corriero; Caterina Longo; Cataldo Pierri; Guadalupe Gimenez; Maria Flavia Gravina; Adriana Giangrande; Stefania Lisco; Massimo Moretti; Francesco De Giosa; Maria Mercurio; Carlotta Nonnis Marzano (Frontiers in Marine Science, 2022)
A widespread and diversified mesophotic system of carbonate bioconstructions along the Southern Adriatic and Ionian Italian coasts is described, providing new data on the distribution, structure and associated megabenthic assemblages of mesophotic Mediterranean bioconstructions. The bioconstructions were detected at six different sites off the coasts of Apulia, in presence of marked morphological escarpments, developing on a basal substrate consisting of meso-Cenozoic carbonate rocks. Two biogenic structure types were observed, one mainly built by the nonsymbiotic scleractinians Phyllangia americana mouchezii and Polycyathus muellerae , at depths between approximately 35 and 55 m, and the other by the oyster Neopycnodonte cochlear , at depths from approximately 40 to 70 m. A total of 52 taxa of megabenthic invertebrates, belonging to 6 phyla, were found on the surface of the mesophotic bioconstructions, thus confirming the role of biodiversity hotspots of these carbonate structures. Megabenthic assemblages showed a remarkable heterogeneity both in pattern of species and abundance, probably depending on both the morphological differences of the seabed and the life traits of the single species. Primary bioconstructors seemed to influence the associated community pattern. This peculiar system deserves sound conservation measures in the light of the holistic ecosystem approach for the management of coastal marine areas.

The Footprints of the Wreckage of the Italian Royal Navy Battleship Leonardo Da Vinci on the Mar Piccolo Sea-Bottom (Taranto, Southern Italy) - Giovanni Scardino; Francesco De Giosa; Marco D’Onghia; Pietro Demonte; Paola Fago; Gianluca Saccotelli; Eliana Valenzano; Massimo Moretti; Raffaele Velardo; Gennaro Capasso; Vera Corbelli; Giuseppe Mastronuzzi (Oceans, 2020)
Over the last two decades, the scientific interest for marine geophysical surveys has shown a huge increase, mostly for multidisciplinary applicability on different studies, from historical heritage to environmental remediation. One of the main research fields carried out through marine geophysical surveys is the study of the wreckage footprints connected to the seabed perturbation. In 2018, a strategic project planned by the Italian National Government Commissioner for the remediation in the Taranto area (Southern Italy) stands as a basic sample for such issues. The project aimed at the detection of anthropogenic impact in the highly polluted Mar Piccolo and Mar Grande basins seabed, through a multidisciplinary approach involving geological, biological, chemical, engineering, and ecological studies. The main purpose of the work was to identify any potential pollution source, focusing on anthropogenic sea-floor features such as uncontrolled dumping, wrecks, or other objects of peculiar origin. To achieve the purpose of the work, field surveys were planned and performed in order to direct a general policy and accurate planning for environmental remediation activities. Different marine geophysics methods were used to characterize the main sea-floor features and to detect each anthropogenic feature. A comparative analysis of a high-resolution dataset allowed to clarify the origin of some deep depressions on the Mar Piccolo sea-bottom, which at the first instance were associated with a natural origin, as the results of the Leonardo Da Vinci wreckage and related recovering activities. High-resolution morphobathymetric, magnetometric, and seismic data revealed the story of the Italian Royal Navy battleship which sunk on 2 August 1916 as a slight footprint on the Mar Piccolo seabed but a deep historical heritage of the city of Taranto. Moreover, final results demonstrate high-resolution marine survey methodologies’ complete applicability to environmental, historical, and scientific issues.

Cytotoxicity and genotoxicity of size-fractionated particulate matter collected in underground workplaces - Elena Guerrera; Luca Dominici; Sara Levorato; Samuele Vannini; Mattia Acito; Cristina Fatigoni; Milena Villarini; Massimo Moretti (Air Quality, Atmosphere & Health, 2019)

Micronuclei and chromosome aberrations in subjects occupationally exposed to antineoplastic drugs: a multicentric approach - Massimo Moretti; Maria Giuseppa Grollino; Sofia Pavanello; Roberta Bonfiglioli; Milena Villarini; Massimo Appolloni; Mariella Carrieri; Laura Sabatini; Luca Dominici; Laura Stronati; Giuseppe Mastrangelo; Anna Barbieri; et al. (International Archives of Occupational and Environmental Health, 2015)

Molecular epidemiology and genetic diversity of human rhinovirus affecting hospitalized children in Rome - Alessandra Pierangeli; Massimo Ciccozzi; Stefano Chiavelli; Carlo Concato; Marta Giovanetti; Eleonora Cella; Lucia Spano; Carolina Scagnolari; Corrado Moretti; Paola Papoff; Maurizio Muraca; Fabio Midulla; et al. (Medical Microbiology and Immunology, 2013)

Mantle and crustal processes in the magmatism of the Campania region: inferences from mineralogy, geochemistry, and Sr–Nd–O isotopes of young hybrid volcanics of the Ischia island (South Italy) - Massimo D’Antonio; Sonia Tonarini; Ilenia Arienzo; Lucia Civetta; Luigi Dallai; Roberto Moretti; Giovanni Orsi; Mariachiara Andria; Alberto Trecalli (Contributions to Mineralogy and Petrology, 2013)

Chlorhexidine MCM-41 Mucoadhesive Tablets for Topical Use - Valeria Ambrogi; Luana Perioli; Fabio Marmottini; Massimo Moretti; Elisa Lollini; Carlo Rossi (Journal of Pharmaceutical Innovation, 2009)

Asymmetrical soft-sediment deformation structures triggered by rapid sedimentation in turbiditic deposits (Late Miocene, Guadix Basin, southern Spain) - Massimo Moretti; Jesús Miguel Soria; Pedro Alfaro; Nicola Walsh (Facies, 2001)